2014
DOI: 10.1021/ef5000694
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles for Enhanced Oil Recovery: Phase Transition of Aluminum-Cross-Linked Partially Hydrolyzed Polyacrylamide under Low-Salinity Conditions by Rheology and Nuclear Magnetic Resonance

Abstract: There is booming interest in the application of nanoparticles for enhanced oil recovery. In this work, a polymer nanoparticle that is generated by cross-linking a high-molecular weight partially hydrolyzed polyacrylamide with aluminum­(III) and known as linked polymer solution (LPS) has been studied. The size and conformational state of LPS particles are influenced by the concentration of Al­(III). To the best our knowledge, there is no current established method for determining the conformational state, i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In our previous study, HPAM and LPS were prepared in a low salinity (i.e., 0.5 wt % NaCl), the distance d CH2‐NHa varied between 3.0 and 4.1 Å, whereas d CH2‐NHb varied between 2.4 and 2.6 Å. However, at higher salinity (5 wt % NaCl), these distances are longer than 5 Å for all concentrations of Al 3+ (see Figure S1 in Supporting Information) and thereby, no cross peak signals.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…In our previous study, HPAM and LPS were prepared in a low salinity (i.e., 0.5 wt % NaCl), the distance d CH2‐NHa varied between 3.0 and 4.1 Å, whereas d CH2‐NHb varied between 2.4 and 2.6 Å. However, at higher salinity (5 wt % NaCl), these distances are longer than 5 Å for all concentrations of Al 3+ (see Figure S1 in Supporting Information) and thereby, no cross peak signals.…”
Section: Resultsmentioning
confidence: 92%
“…The diffusion coefficient of HPAM solution prepared in 5 wt % NaCl diffuse faster than HPAM solution made in 0.5 wt % NaCl (log D = −12.0 m 2 /s) . This indicates that the effective hydrodynamic radius of 600 ppm HPAM is larger in 0.5 wt % NaCl, despite the re‐expansion occurring at 5 wt % NaCl.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, for the influence on the cross-linked polymer, that of Ca 2+ is the biggest, then Mg 2+ , the least being Na + . In 2014, Kedir et al [25] investigated that phase transition of aluminum cross-linked HPAM under a low salinity condition and revealed that the phase transition is a stepwise process. The first step is the transition from a random polymer coil to structured coils, the second step is that the networked weak gel is formed by coil aggregates above the threshold concentration.…”
Section: Introductionmentioning
confidence: 99%